Characterization and phylogenetic analysis of the complete chloroplast genome of Actinidia latifolia (Actinidiaceae). Issue 2 (1st February 2021) - Yang, Aihong; Hu, Miao; Liu, Tengyun; Liu, Shujuan; Zhou, Hua; Yu, Faxin
Abstract: The complete chloroplast (cp) genome of Actinidia latifolia was sequenced and assembled using Illumina pair-end sequencing data. The cp genome is 157, 021 bp in length and comprises a large single copy (LSC) region of 88, 557 bp and a small single copy (SSC) region of 21, 562 bp separated by two inverted repeat (IR) regions of 23, 451 bp. A total of 113 unique genes were identified, including 79 protein-coding genes, 30 tRNA genes, and four rRNA genes. Phylogenetic analysis based on cp genomes of 20 Actinidiaceae species revealed that A. latifolia was evolutionarily close to A. eriantha, A. styracifolia, and A. fulvicoma.